THE POLITICS OF DISSENT: THE CATHOLIC CHURCH AND THE CONFLICT IN NORTHERN IRELAND. Issue 2 (April 2020) - Power, Maria
Abstract : The conflict in Northern Ireland altered the way in which the Catholic Church in the region behaved in the public square. The main proponent of this was Cardinal Cahal Daly, the only bishop to have served throughout the troubles in Northern Ireland. This article will explore the methods he used before illustrating their implementation by examining his work on prisoners and human rights. It will argue that human flourishing and dignity lay at the heart of all of the Catholic Church's interventions in the public square.